Open-flap versus minimally invasive esthetic crown lengthening: Systematic review and meta-analysis - Blake Crosby; Mira Ghaly; Gregory Griffin; Brittany Ange; Ahmed R El-Awady (Elsevier, 2023)
Background: Esthetic crown lengthening is often performed to address excessive gingival display due to altered passive eruption. When bone reduction is required, most surgeons approach this procedure with an open flap approach. The aim of this systematic review and meta-analysis is to compare the outcomes of an open flap versus a more conservative closed flap approach. Methods: An electronic search of Medline Pubmed and Cochrane library was conducted with "Does a flapless approach with piezoelectric to crown lengthening provide superior results than the traditional crown lengthening approach?" as the focused question. After reviewing the selected articles, the data was extracted to evaluate the relative gingival margin as the primary outcome variable. Statistical analysis was performed according to PRISMA guidelines for meta-analysis. Results: Out of 65 studies, 4 prospective randomized controlled clinical trials met the inclusion criteria and were included for further analysis. The estimated standard difference in means for all studies was 0.349 (95% CI: (0.133, 0.565), p = 0.002) indicating that the open flap had a larger change in gingival margin from baseline to 3 months than the flapless technique. The results of Cochran's Q concluded no evidence of heterogeneity (Cochran's Q = 4.745, d.f.=5, p-value=0.448). The funnel plots and fail-safe analyses concluded no evidence of publication bias. Conclusions: A minimally invasive closed flap approach using piezoelectric instruments, in the appropriate cases, seem to have better gingival margin stability at 3 months and excellent patient centered outcomes. Further well-designed studies are needed to shed more light on the validity of this technique.